Sense of Place, Sense of self: Sharing place through the lens of food, culture and the sensory embodiment of space - Bardien, Kaamilah (School of Architecture, Planning and Geomatics, 2024)
Cooking is a sensory experience. It is possible to cook without sight, I've seen it be done, but it is much more challenging to cook, or rather cook well, without the sense of smell, touch and taste. Those three senses are the most important for cooking something delicious. Eating is a part of everyday life. It is something we cannot go without so it's best to enjoy the moments that make up such a big part of our lives. That being said, sight has been and continues to be the most dominant sense, followed by hearing. I will not argue that sight is not important, but rather that the way that we experience the world should not focus vehemently on the sense of sight because when our other senses are engaged too, it can make an experience richer and more memorable. Within this dissertation, I hold near personal memories of Bo-Kaap, my family, and interpretations of home and sense of place. Through this paper, I will explore how I can share culture, place, and a sense of place through the lens of food with a key focus on the sensory embodiment of space. I will look closely at how place is defined and how we form attachments to place. The theoretical analysis will include how we define home. I will share my own experiences and narratives of home, how food and cooking have shaped important parts of myself and how I connect with others through food. I will focus on memory as a leading narrative of how food and culture are shared. Sensory experiences play a big part in the formation of memory. When we are born we use touch to communicate with the world. We use our senses to guide us and protect us from harm. It is important for designers to take into account how users of spaces experience it with their senses such as touch, smell and hearing. Taste is not a key way in which we experience design but it is an important way in which we can find enjoyment since eating is part of everyday life. I will look into how a designer can create a sensory experience for the user focusing on the senses mentioned. Bo-Kaap is the place at which Islam was introduced to South Africa. In my technical analysis, I will look to the past to learn more about how the architecture of Bo-Kaap developed into what it is today. I will examine what exists and how the past informed the first religious building, the Auwal Mosque, and how it changed since then. I will then examine the differences between the Auwal Mosque, and its sensory qualities, versus the typical residential buildings. the key elements and features of what is commonly understood as Bo-Kaap's architectural language. I will follow up with a repurposed space that has the sensory qualities I hope to convey. This analysis will show me a way in which the new can celebrate the old. It was designed to keep the user's experience at the centre, then offered as a gift to all those who will come to visit it so I will learn how a gift like that can be offered to the public. These case studies will inform my design outcomes. Lastly, I will take the reader through my design process, development, and the outcomes of my research.